PELAKSANAAN AKAD PEMBIAYAAN MURABAHAHAL-WAKALAH PADA PEMBIAYAAN WARUNG MIKRO DIPT. BANK SYARIAH MANDIRI CABANG MEDAN - DESY WULANDARI WIJAYA (PREMISE LAW JURNAL, 2015)
One of the financing products in Syariah Banking is Murabahah Al-Wakalah financing found in the Fatwa of National Syariah Council No.04/DSN-MUI/IV/2000 on Murabahah and No.10/DSN-MUI/IV/2000 on Al-Wakalah. This Murabahah Al-Wakalah agreement is applied at Bank Syariah Mandiri, Medan Branch in implementing the micro financing distributed to the community members. The result of this study showed that the agreement of Murabahah Al-Wakalah was the one used for the financing product of micro-shop at Bank Syariah Mandiri.  Micro-shop is the financing given by Bank Syariah Mandiri to the prospective customers either individual or business entity to finance the  need of their business through working capital financing, investment financing, people’s business financing, early basic,intermediate and major financing. In which, the financing used the agreement of Murabahah Al-Wakalah as their payment agreement contract. Keywords : Murabahah Agreement, Al-Wakalah Agreement, Bank Syariah Mandiri Medan Branch